PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BOARD GAME MAGIC SHOP PADA MATERI ARITMATIKA SOSIAL - Qisma, Nina; Afifah, Ani; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2024)
This research has an impact on the development of board game media which is developed not only in the form of monopoly and snakes and ladders. The "magic shop" board game media is a game board media that contains a summary of material in the form of social arithmetic sub-chapter formulas and a game board that contains practice questions that students must complete. This research uses an R&D research development model which includes 6 steps, namely potential and problems, data collection, product design, design validation, design revision, product testing. The research subjects were grade 7 junior high school students. The level of media practicality was based on a questionnaire filled out by students and was assessed as having very practical results with an average score of 82.70% and the level of media effectiveness based on tests that had been given had very effective results with an average score. 85.67%.